1997
DOI: 10.1046/j.1570-7458.1997.00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Melon resistance to the aphid Aphis gossypii: behavioural analysis and chemical correlations with nitrogenous compounds

Abstract: In the melon, the Vat (monogenic, dominant) resistance gene governs both an antixenotic reaction to the melon aphid Aphis gossypii Glover (Homoptera, Aphididae) and a resistance to non-persistent virus transmission, restricted to this vector species. We investigated the behavioural features and tissue localisation of the antixenosis resistance by the electrical penetration graph technique (EPG, DC system). We also compared the chemical composition in amino compounds and proteins of the phloem sap collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 28 publications
(57 reference statements)
4
64
1
3
Order By: Relevance
“…Unlike our study, however, preinfestation of a susceptible cultivar (unrelated to the resistant cultivar) caused an increase in sap ingestion, suggesting that aphids induced changes in the host plant's physiology leading to enhanced susceptibility. Our results and those of Sauge et al contrast with those of Chen et al (1997), who observed no effect of prior infestation on the feeding behavior of A. gossypii on melon near-isogenic lines, with or without the Vat gene.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Unlike our study, however, preinfestation of a susceptible cultivar (unrelated to the resistant cultivar) caused an increase in sap ingestion, suggesting that aphids induced changes in the host plant's physiology leading to enhanced susceptibility. Our results and those of Sauge et al contrast with those of Chen et al (1997), who observed no effect of prior infestation on the feeding behavior of A. gossypii on melon near-isogenic lines, with or without the Vat gene.…”
Section: Discussioncontrasting
confidence: 97%
“…Interestingly, they found no preference for either melon genotype at 4 h after release, but a highly significant preference for the susceptible genotype at 24 and 48 h after release. Like AKR-mediated resistance, the resistance mechanism in melon was later shown to be phloem localized (Kennedy et al, 1978;Chen et al, 1997;Klingler et al, 1998), suggesting that time was spent probing phloem tissue before alatae chose between alternative hosts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant differences were found at day 5 in the tolerant genotype. In plants, all of the aphid resistance genes, reported so far, encode nucleotide binding site-LRR proteins (Crute and Dunn 1980;Chen et al 1997;Rossi et al 1998;Milligan et al 1998;Nombela et al 2003;Wroblewski et al 2007). These large, and often abundant, proteins aid in the detection of diverse pathogens including bacteria, viruses, fungi, insects, and nematodes.…”
Section: Analysis Of Differentially Expressed Genesmentioning
confidence: 99%
“…When aphids penetrate a SE with their stylet tips, they start injecting watery saliva into the SE (20), and, if the penetration is successful, after a period of secretion of watery saliva, the aphid then begins ingesting sap from the SE. When feeding on resistant plants, the transition from salivation to ingestion often fails to occur or, if ingestion does occur, the aphid often reverts back to salivation after a brief ingestion period (21,22).…”
mentioning
confidence: 99%